Organisational citizenship behaviour: conditional, gendered, obligatory, silently mandatory? - Fish, Kelly (Organisational Psychology, 2025)
The research presented in this dissertation explores the relationships between income, pay satisfaction, and Organisational Citizenship Behaviour (OCB) among women and men in low to middle-income employment. A descriptive research design was implemented using secondary, cross-sectional survey data (N = 1,566). The dataset included participants from each South African province. Per province, the number of participants was proportionate to the percentage of South Africa's population living there. The results indicated that differently to the expected two OCB dimensions, three OCB dimensions emerged: OCB-I (helping behaviour toward individuals), OCB-O (an absence of unproductive work behaviours which would harm the organisation), and OCB-I-O (consideration behaviours towards individuals and the organisation). As hypothesised, income was positively correlated with pay satisfaction, and greater income was related to greater levels of OCB. However, pay satisfaction and OCB were not correlated, and women and men had similar income levels, pay satisfaction, and OCB. Gender did not moderate the relationships between income and OCB, nor between pay satisfaction and OCB. The results highlight that regardless of how satisfied employees are with their pay, it is the actual income amount that is related to OCB. These findings indicate that employers could pay more to increase the chances that employees will perform OCBs that benefit the organisation.